RELEVANCE AND USE OF THE RUSSIAN LANGUAGE IN THE MODERN WORLD - Ashurova Saida Azadbekovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article gives arguments on how relevant and important the Russian language is for communication between peoples. The usefulness of the Russian language is proved by its role in the culture and science of all mankind, since the language is a common means of communication and information transmission.